Elemento(III) Derivatives of N-(2-Hydroxy- 6-Methyl Benzyl) Valine - P. Pande, Ashutosh; Chandra, Madhup (Asian Journal of Chemistry, 2012)
Several elemento(III) viz. boron, aluminium, iron, arsenic and antimony derivatives of N-(2-hydroxy-6-methyl benzyl) valine have been prepared by alcoholysis reactions involving the interaction of the corresponding elemento(III) isopropoxide and the latter in 1:1:,1:2 and 1:3 molar ratios in benzene medium. The compounds thus prepared were obtained as coloured solids and out of them those containing isopropoxy group were found to be hygroscopic. All these compounds were characterized by azeotrope and elemental analyses, as well as by IR and PMR spectral measurements.